1996
DOI: 10.1097/00000658-199602000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of Laparoscopic-Assisted Large-Bowel Excision for Cancer

Abstract: ObjectiveThe authors described their experience with laparoscopic-assisted colorectal resection for colorectal carcinoma, both curative and palliative, with emphasis on patient selection. The techniques of the operations were described. Summary Background Data ResultsFourteen of 83 patients eventually required conversion to open surgery. The median operative time was 180 minutes. The patients could return to a normal diet in a median of 4 days. The median number of doses of analgesics required was two, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
0
4

Year Published

1997
1997
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(91 citation statements)
references
References 21 publications
5
82
0
4
Order By: Relevance
“…Our laparoscopic approach has been reported previously [6], but there were some modifications in the later cases. Initially we put the patients in the Lloyd Davies position.…”
Section: Methodsmentioning
confidence: 99%
“…Our laparoscopic approach has been reported previously [6], but there were some modifications in the later cases. Initially we put the patients in the Lloyd Davies position.…”
Section: Methodsmentioning
confidence: 99%
“…Since similar findings had been described for other intraabdominal malignancies including pancreatic, ovarian, and gallbladder cancer [41], it was not clear whether these types of recurrences were an inevitable consequence of the minimally invasive techniques or perhaps related to a learning experience. A review of the reported rates of wound tumor recurrence following laparoscopic colorectal surgery (Table III) [9,10,31,32,37,38,42,48,58,70,72,73] highlights several points regarding this issue. It is clear that in some earlier studies the incidence of wound tumor implants far exceeded that reported for open surgery.…”
Section: Altered Tumor Spreadmentioning
confidence: 99%
“…Since the first publication by Alexander et al [7] in The Lancet in 1993, there have been a lot of reports about such tumor inoculations [8][9][10] (table 11). In our series, we observed 2 of 58 patients (= 3.4%) with such a metastasis.…”
Section: Discussionmentioning
confidence: 99%